Agrosilvopasture System in Taratara Village, West Tomohon District, Tomohon City, North Sulawesi - Euis Francoise S Pangemanan; Fabiola Baby Saroinsong; Octavianus Yohanis Pandey; Semuel Paulus Ratag (Universitas Sam Ratulangi, 2025)
The agrosilvopastura system is one part of an efficient agroforestry system to be applied in integrated landscape management. The community in Taratara Village, West Tomohon Sub-district, North Sulawesi Province has a majority of people who work as farmers. Some of the people of Taratara Village who work as farmers also raise livestock on the same plot of land with various crops. This indicates that the community group applies the agrosilvopastura system in their landscape management. This study aims to assess the pattern of agrosilvopastura application in Taratara Village. The research method used was a survey method by means of interviews using a questionnaire as a guide and field observations. The survey results show that, in Taratara Village there are as many as 5 farmers who apply agrosilvopastura patterns. The results showed that the agrosilvopastura pattern in Taratara Village combines the cultivation of forestry crops and agricultural crops together with the raising of livestock (pigs, ducks, chickens, cows) on the same land. Livestock are raised with various methods and feeds that are adapted to the type of livestock. Woody crops are planted randomly and regularly, and food crops are also planted regularly and regularly among woody crops. Farmers who apply the agrosilvopastura pattern in Taratara Village choose this pattern because of its advantages, namely 1) getting more optimal results with the presence of trees, food crops and livestock on the same land, 2) parts of cultivated plants that are not consumed or poor harvests can be used as animal food, 3) more efficient land utilization, 4) the acquisition of products (harvestable products) is more diverse, 5) certain livestock raised can be utilized for their energy, 6) improving soil fertility.